The Influence of the Cooperative Learning Model Type Numbered Heads Together (NHT) on the Mathematical Creative Thinking Ability of Students in Class VIII of Trisakti Private Junior High School, Pematang Siantar - Sitanggang, Herni Lestaria; Sidabutar, Ropinus (Lembaga Riset Mutiara Akbar, 2023)
The purpose of this study was to determine the effect of using the Numbered Heads Together (NHT) type cooperative learning model on students' mathematical creative thinking skills in class VIII of SMP Swasta Trisakti Pematang Siantar. This research design uses One-Shoot Case Study. The population in this study were all VIII grade students of Trisakti Pematang Siantar Private Junior High School T.A 2023/2024, and the sample in this study were all VIII grade students of Trisakti Pematang Siantar Private Junior High School totaling 30 students. The instruments used in this study are validity, reliability, level of difficulty of test items and distinguishing power of test items. The data obtained were then analyzed using data analysis techniques obtained the average value of the results of the Numbered Heads Together (NHT) learning model 85.63 and the average mathematical creative thinking ability of students 16.384. The results of hypothesis testing after obtaining t-count = 26.134 and t-table = 2.048. This means that the tcount is greater than the ttable which shows the hypothesis H0 is rejected and Ha is accepted. Based on this description, it is concluded that the use of the Numbered Heads Together (NHT) learning model has an influence on students' mathematical creative thinking skills in learning the Two-Variable Linear Equation System (SPLDV) in class VIII SMP Swasta Trisakti Pematang Siantar.